PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA GURU DI SEKOLAH MENENGAH PERTAMA - Muhtasor; Hasan Hariri; Sowiyah; Handoko (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2025)
This study aims to analyze the effect of organizational commitment on the performance of public junior high school teachers in Pringsewu Regency. The research method used is quantitative with an ex post facto design and correlational method. The research population includes 822 teachers, with a sample of 274 teachers selected using Proportionated Random Sampling. Data analysis was conducted using simple linear regression and partial t-tests. The results showed that organizational commitment had a positive and significant effect on teacher performance, with a contribution of 74.9%. These findings indicate that teachers with high commitment work more professionally, are more disciplined, and are more responsible, thereby improving the quality of learning.